2018
DOI: 10.1103/physrevmaterials.2.124204
|View full text |Cite
|
Sign up to set email alerts
|

Second-neighbor electron hopping and pressure induced topological quantum phase transition in insulating cubic perovskites

Abstract: Perovskite structure is one of the five symmetry families suitable for exhibiting topological insulator phase. However, none of the halides and oxides stabilizing in this structure exhibit the same. Through density functional calculations on cubic perovskites (CsSnX3; X = Cl, Br, and I), we predict a band insulator -Dirac semimetal -topological insulator phase transition with uniform compression. With the aid of a Slater-Koster tight binding Hamiltonian, we show that, apart from the valence electron count, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…Though the universality of the band structure arises from the nearest-neighbor B-{s, p}-X-p covalent interactions as discussed in the previous paragraph, the second neighbor B-{s, p}-B-{s, p} interactions are found to be the driving force for engineering the bandgap as well as construing non-trivial phases [13]. In the ground state, the second neighbor interaction strength is less than 1eV (almost one-third of nearest neighbor interaction) [13,19] which can be varied and made anisotropic easily through strain and will be discussed in the following sub-section.…”
Section: Structural and Computational Detailsmentioning
confidence: 94%
See 4 more Smart Citations
“…Though the universality of the band structure arises from the nearest-neighbor B-{s, p}-X-p covalent interactions as discussed in the previous paragraph, the second neighbor B-{s, p}-B-{s, p} interactions are found to be the driving force for engineering the bandgap as well as construing non-trivial phases [13]. In the ground state, the second neighbor interaction strength is less than 1eV (almost one-third of nearest neighbor interaction) [13,19] which can be varied and made anisotropic easily through strain and will be discussed in the following sub-section.…”
Section: Structural and Computational Detailsmentioning
confidence: 94%
“…Considering the α-phase, for any halide and oxide perovskites ABX 3 we have shown that bonding and antibonding bands emerge out of strong B-{s, p}-X-p nearest neighbor covalent interactions. [13,19] The anti-bonding and bonding bands are separated by a set of X-p dominated non-bonding bands. Furthermore, both bonding and antibonding spectrum have four bands with the lower one is formed by the B-s-X-p hybridized states and the upper three are formed by the B-p-X-p hyrbridized states.…”
Section: Structural and Computational Detailsmentioning
confidence: 99%
See 3 more Smart Citations